Swollenin from Trichoderma reesei exhibits hydrolytic activity against cellulosic substrates with features of both endoglucanases and cellobiohydrolases. (April 2015) - Andberg, Martina; Penttilä, Merja; Saloheimo, Markku
Highlights: The T. reesei swollenin SWOI and its catalytic domain was produced and characterised. SWOI showed activity against β-1, 4 linked cellulosic substrates. SWOI decreased the viscosity of polymeric substrates. The major cleavage product from β-glucan and cello-oligosaccharides was cellobiose. SWOI showed similarities with action of both endoglucanases and cellobiohydrolases. Abstract: The cellulolytic and hemicellulolytic enzymes of Trichoderma reesei comprise one of the best characterised enzyme systems involved in lignocellulose degradation. In this paper, swollenin (SWOI), a protein recognised based on its sequence similarity with plant expansins, has been characterised. SWOI and its catalytic domain were subjected to analysis of their hydrolytic activity on different soluble carbohydrate polymers. By measuring the production of reducing ends, zymogram-, and viscosity analysis, SWOI was shown to have activity on substrates containing β-1, 4 glucosidic bonds, i.e. carboxymethyl cellulose, hydroxyethyl cellulose and β-glucan. The formation of oligosaccharides from β-glucan was analysed by HPLC and showed cellobiose as the main reaction product. SWOI was also able to hydrolyse soluble cello-oligosaccharides and the products formed were all consistent with SWOI cleaving a cellobiose unit off the substrate. In conclusion, the T. reesei swollenin showed a unique mode of action with similarities with action of both endoglucanases and cellobiohydrolases.